Oxidative Folding of Peptides and Proteins - Buchner, Johannes; Ed. Moroder,Luis; Ed (RSC Biomolecular Sciences., 2009)
With contributions from experts in the field, this book provides a comprehensive overview of the oxidative folding of cysteine-rich peptides.